FATHER OF THE FRENCH REVOLUTION - Hamzayev , Ravshanbek Erkinjon oʻgʻli (Educational Research in Universal Sciences, 2023)
This article is about the person named the Father of French Revolution, a French revolutionary, one of the most famous and influential representatives of the Great French Revolution, an Artois democrat, the president of the French National Convention.